1999
DOI: 10.1161/01.str.30.5.1025
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation Between Pattern of Collateralization and Misery Perfusion in Patients With Carotid Occlusion

Abstract: Background and Purpose-Misery perfusion, identified by increased oxygen extraction fraction (OEF), predicts subsequent stroke in patients with carotid occlusion. The purpose of this investigation was to determine the relationship of angiographic findings to increased OEF in these patients. Methods-Forty-seven patients with carotid occlusion were studied with cerebral angiography and positron emission tomography (PET). The following angiographic data were collected blind to PET results: (1) pial collateralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 52 publications
2
34
0
2
Order By: Relevance
“…This finding is in accordance with the results of a recent study that demonstrated the lack of correlation between pattern of collateralization, studied by cerebral angiography, and increased oxygen extraction fraction, measured by PET in patients with ICA occlusion. 37 In our study, as shown in Figure 3, the absence of any collateral pathways or the presence of all 3 collateral pathways were linked to a strongly impaired or normal cerebral VMR, respectively. These conditions were correlated with a high or low probability of a stroke, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…This finding is in accordance with the results of a recent study that demonstrated the lack of correlation between pattern of collateralization, studied by cerebral angiography, and increased oxygen extraction fraction, measured by PET in patients with ICA occlusion. 37 In our study, as shown in Figure 3, the absence of any collateral pathways or the presence of all 3 collateral pathways were linked to a strongly impaired or normal cerebral VMR, respectively. These conditions were correlated with a high or low probability of a stroke, respectively.…”
Section: Discussionsupporting
confidence: 61%
“…12 Unexpectedly, angiographic demonstration of collaterals, or lack of collaterals, has not been shown to correlate with cerebral perfusion studies. 17 Blood supply to regions of the brain through the collateral circulation occurs with increasing severity of ICA stenosis and occlusion. To what extent collaterals modify the risk of stroke, independently of increasing stenoses, is unknown.…”
mentioning
confidence: 99%
“…Cerebral hypo perfusion is one of main clinical manifestations in patients with severe CAS, and can be measured directly by various imaging techniques, such as CT perfusion [12,16,20], MR perfusion [14,21,22], single photon emission computed tomography [23], and positron emission tomography [24,25] imaging. In patients with mildly decreased cerebral perfusion pressure, the overall cerebral perfusion can be maintained by autoregulatory mechanisms; the cerebral blood volume (CBV), TTP and even oxygen extraction fraction (OEF) are gradually increased while the CBF remains unchanged or slightly decreased [26].…”
Section: Ophthalmic Artery Flow and Cerebral Blood Flowmentioning
confidence: 99%
“…With regard to the influence of reversed OA flow on cerebral perfusion, some studies suggest that recruitment of secondary collaterals can protect the brain against further ischemic injury by augmenting blood supply [14,21,27], while others regard secondary collaterals as a marker of insufficient overall cerebral perfusion [4,13,24,28]. The presence of reversed OA flow is beneficial to regional CBF supply in patients with symptomatic unilateral carotid artery occlusion [14].…”
Section: Ophthalmic Artery Flow and Cerebral Blood Flowmentioning
confidence: 99%